2011
DOI: 10.3340/jkns.2011.50.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Fluid Collection after Cranioplasty : Fate and Predictive Factors

Abstract: We conducted retrospective collection of demographic, clinical, and radiographic data in 59 patients who underwent a first cranioplasty following decompressive craniectomy during a period of 6 years, between January 2004 and December 2009. Patients underwent decompressive craniectomy for the control of increased intracranial pressure.The decision to undertake cranioplasty depended on the judgment of each individual surgeon. Although operative techniques of cranioplasty were different among neurosurgeons, bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 15 publications
3
35
1
5
Order By: Relevance
“…Another study [19] that reported the rates of new ipsilateral hematoma in ICH and SAH patients separately found a similar overall rate in these patients at 7.3 % (4/55), in 15.4 % (2/13), and 4.8 % (2/42) of ICH and SAH patients, respectively. In studies in which the indication for DC was not specified or not stratified [12, 64, 121, 124128, 135, 137], the frequency of new ipsilateral hematomas after cranioplasty was 3.0 % (61/2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study [19] that reported the rates of new ipsilateral hematoma in ICH and SAH patients separately found a similar overall rate in these patients at 7.3 % (4/55), in 15.4 % (2/13), and 4.8 % (2/42) of ICH and SAH patients, respectively. In studies in which the indication for DC was not specified or not stratified [12, 64, 121, 124128, 135, 137], the frequency of new ipsilateral hematomas after cranioplasty was 3.0 % (61/2016).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies reported rates of infection after cranioplasty, but the anatomic location was not specified [1114, 29, 35, 66, 92, 101, 104, 109, 121, 124, 126, 128, 135, 141, 144, 146, 152156]. Overall, the rates reported in these studies were 7.3 % (152/2092).…”
Section: Resultsmentioning
confidence: 99%
“…Operation way was decided by neurosurgeons before operation and the decision was supplied to the manufacturing company for the construction of titanium mesh. During CP, some points must be concerned: first, subgaleal space of the scalp should be dissected to release any tension that might occur during wound closure; second, while reaching the space between dural and temporalis muscle, dural tearing should be avoided; third, dural tenting sutures were placed in the center of ellipse and circumferentially in the frontal, parietal, and temporal regions to obliterate the dead space 7,8 (Fig. 2B-D); fourth, during CP with reflection of temporalis muscle, dissected muscle was reattached to the titanium mesh in fan shaped (mimicking its original anatomy; Fig.…”
Section: Surgical Protocolmentioning
confidence: 99%
“…8 In brief, a headband is placed around the head and marked with 2 adjustable points, on which denotes the nasion and the other which denotes the inion. A digital camera takes a picture of the head from a vertex view.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Although several studies have focused on the risk and predictors of infection and bleeding after cranioplasty, [12][13][14][15] research is sparse regarding the predictive factors associated with other types of postoperative complications. 7 Cited positive predictors of complications after cranioplasty include a history of irradiation, preoperative infection, 9 pneumocephalus, 16 nicotine abuse, age older than 60 years, lower Glasgow Outcome Scale, 19 and bifrontal cranioplasty. 20,21 However, despite a large body of research on perioperative anticoagulation, and the growing number of patients diagnosed with thromboembolic disease each year, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] no study to date has investigated the impact of perioperative anticoagulant therapy on complications following cranioplasty reconstruction.…”
mentioning
confidence: 99%